2020
DOI: 10.1016/j.neubiorev.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cognition through pharmacological and environmental interventions: Examples from preclinical models of neurodevelopmental disorders

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 356 publications
0
11
0
Order By: Relevance
“…The extracellular-signal regulated kinase (ERK) cascade belongs to the mitogen-activated protein kinase (MAPK) superfamily, a class of highly conserved serine/threonine kinases, originally implicated in cell proliferation, survival, and apoptosis (Mebratu and Tesfaigzi, 2009;Roskoski, 2012). Over the last two decades, considerable attention has been pointed to the multifaceted role of this signaling cascade in a variety of brain functions, from learning and consolidation of long-term memories to drug addiction and neuropsychiatric disorders (Mazzucchelli et al, 2002;Trifilieff et al, 2007;Hart and Balleine, 2016;Krawczyk et al, 2016;Borrie et al, 2017;Morè et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular-signal regulated kinase (ERK) cascade belongs to the mitogen-activated protein kinase (MAPK) superfamily, a class of highly conserved serine/threonine kinases, originally implicated in cell proliferation, survival, and apoptosis (Mebratu and Tesfaigzi, 2009;Roskoski, 2012). Over the last two decades, considerable attention has been pointed to the multifaceted role of this signaling cascade in a variety of brain functions, from learning and consolidation of long-term memories to drug addiction and neuropsychiatric disorders (Mazzucchelli et al, 2002;Trifilieff et al, 2007;Hart and Balleine, 2016;Krawczyk et al, 2016;Borrie et al, 2017;Morè et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many studies point to a higher risk on impaired mnemonic function, aberrant reward-based decision-making and enhanced anxiety-related behavior after early life adversity ( Delavari et al, 2016 ; Herzberg and Gunnar, 2019 ; Woldemichael et al, 2014 ). Conversely, a favorable rearing environment might have beneficial effects on cognition, emotionality and response to stress ( Cirulli et al, 2010 ; Morè et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, the Ras-ERK pathway has been proposed to be the primary mediator of in vivo adaptations to the environment [4][5][6]. Previous work in mice has shown that much of the cognitive enhancing effects of environmental enrichment act via the downstream Ras-ERK signalling kinase MSK1 and a relevant portion of spatial cognitive flexibility is mediated by the transcription factor CREB phosphorylation [4,7,8]. It remains still an open question whether some key aspects of spatial learning & memory and procedural learning might be governed by different molecular pathways than those controlling social cognition [9].…”
Section: Introductionmentioning
confidence: 99%
“…[7,[34][35][36][37][38]. LC-MS/MS analysis identified 977 proteins from the hippocampi and frontal lobes of mice from positively and negatively enriched groups and determined their normalised abundance (see supplementary data for raw data tables).Of the total number of proteins identified, none were increased or decreased in the hippocampus (supplementary data).…”
mentioning
confidence: 99%
See 1 more Smart Citation